Preventing Foodborne Illness: E. coli O157:H7 - Keith R. Schneider; Renée M. Goodrich; Melissa A. Kirby (EDIS)
This is one in a series of fact sheets discussing common foodborne pathogens of interest to food handlers, processors, and retailers.  For related publications, visit http://edis.ifas.ufl.edu/topic_foodborne_illness. This document is FSHN031, one of a series of the Food Science and Human Nutrition Department, Florida Cooperative Extension Service, IFAS, University of Florida. Publication: January 2003.